Effect of ionic liquid on thermo-physical properties of bamboo biomass - Muhammad, N. (Springer Verlag, 2015)
In this work, EmimGly ionic liquid was used for the pretreatment of bamboo biomass followed by regeneration of cellulose-rich material. Thermal degradation study of untreated bamboo and cellulose-rich material was carried out under dynamic condition using thermogravimetric analysis. Free kinetics models of Kissinger, Ozawa, FlynnâWallâOzawa, and KissingerâAkahiraâSunose were used to determine the kinetic parameters of thermal degradation process. The pattern of activation energy (Ea) values with respect to % conversion values was noted different for the aforementioned models. The Ea calculated using the Kissinger method were 184 and 156Â kJÂ molâ1, and Ozawa method were 185 and 157Â kJÂ molâ1 of untreated and treated sample of bamboo, respectively, while the values of Ea calculated by FlynnâWallâOzawa and KissingerâAkahiraâSunose were 71.7â203.4Â kJÂ molâ1 and 281.7â230.7Â kJÂ molâ1 for untreated and treated sample of bamboo, respectively. Calorific and CHNS values of both untreated and regenerated cellulose-rich material were measured by bomb calorimeter and elemental analyzer (CHNS), respectively. Both the calorific value and carbon content of the regenerated cellulose-rich material (15.62Â J/kg, 37.86Â %, respectively) were found to be less than those of untreated bamboo (17.40Â J/kg and 43.14Â %, respectively). The bamboo and regenerated cellulose-rich material were investigated by X-ray diffraction and X-ray Photoelectron Spectroscopy, and changes in the cellulose crystalline structure were correlated with thermal degradation behavior and kinetics parameters. Â© 2015, Springer-Verlag Berlin Heidelberg.